Analisis Tren Viral Di Tiktok Sebagai Sarana Promosi Viva Cosmetics - Agustin, Amanda Fia; Iryanti, Endang (CV. ITTC INDONESIA, 2025)
This study aims to analyze the role of viral trends on TikTok as a promotional tool for Viva Cosmetics. The background of this research is based on the rapid growth of TikTok as an effective social media platform for marketing products through creative and viral content. TikTok serves as a medium that enables brands to interact directly with audiences through engaging and informative short videos. The research method used is a qualitative approach with data collection techniques in the form of observation and in-depth interviews with Viva Cosmetics' internal parties and active TikTok consumers. The results show that leveraging viral trends, producing engaging content, and collaborating with relevant creators play significant roles in increasing brand awareness and product sales. The use of popular hashtags and trending challenges has also proven effective in capturing audience attention and driving purchase decisions. Additionally, consumer trust is further enhanced through authentic product reviews from TikTok creators. These findings demonstrate that marketing strategies based on viral trends on TikTok can strengthen brand image, increase consumer loyalty, and positively impact Viva Cosmetics' sales performance.